Thinking about journalism beyond technology (Intercom - Brazilian Journal of Communication Sciences, 2024)
Born in 1946, Michael Schudson has been one of the most referenced names in the field of journalism studies since the publication of Discovering the news (1978) — a classic that was translated into Portuguese by Editora Vozes in 2010. The result of his doctorate at Harvard, the book is an analysis of the emergence of the ideal of objectivity in the North American press at the end of the 19th century, and develops the argument that its crystallization as a journalistic value occurred after the First World War, as a rhetorical defense against the growing influence of government propaganda and corporate publications.This and other contributions that followed guaranteed him a distinguished academic career, through the University of Chicago and the University of California, San Diego, where he became professor emeritus after almost 30 years of work. In 2009, he began teaching full-time at the pioneering Columbia Journalism School. In the following interview, conducted in November 2021 and revisited in July 2024, we talk about the work developed as a long-time researcher in the field.